Análisis de los ingresos, gastos y su efecto en el presupuesto del Gobierno Autónomo Descentralizado del Cantón Babahoyo del año 2019 - Colombatti Ramirez, Yurisleidi Arlina (2020)
This writing details the problem that arises in the Decentralized Autonomous Government of the Babahoyo Canton regarding the management of income and expenses and its effect with the budget for the year 2019, the problem that this management reflects is that not always and in some certificates The budgetary budget is executed, either in income or expenses, however the lack of its total collection with regard to income not only affects the liquidity of the company in the current year in this case 2019, but also in the coming year (current year), taking into account that the factors that could influence the coming year have not yet been determined, among the factors that influenced the total collection is the lack of payment compliance of the taxpayers, specifically with the payments of property tax, which are the highest items, an incorrect income management would make it difficult in a certain percentage with the fulfillment of obligations such as the of public works that seeks to satisfy the needs of the community, in the case of investment works that represent infrastructure works, it is important to highlight that they make projections about how much will be spent according to the contract with the contracting companies, However, the need to disburse extra money to this event usually arises, it is called complementary contracts or new items are also created, it must be emphasized that within the administration expenses the same problem also occurs since there are certain items with amounts of money that exceeds the budgeted amount.